Improving English Language Speaking Skills Using â€œAbsyakâ€ On-Line Learning Model for Second Semester in Higher Education - Syakur, Abd.; Sugirin, Sugirin; Margana, Margana; Junining, Esti; Sabat, Yulianto (BIRCU, 2020)
This study aims to improve students' speaking skills. The research sample consisted of 30 students (20 female students and 8 male students) all of whom were studying English, the majority of the sample were second semester students, the form of this study was to analyze (1) teaching and learning plans to speak through the task of information gaps that exist in